Bilingual education in the Intermediate Educational System: comparative perspective between Brazil and Peru - Aranibar Ramos, Edgar Romario (2025)
In the vast South American region, profound cultural and linguistic diversity gives rise to striking educational contrasts. This study aims to compare bilingual educational policies and practices in Brazil and Peru, exploring their normative and historical foundations, as well as the attention given to indigenous communities. The importance of analysing socio-educational dynamics in multicultural and multilingual environments is highlighted, along with the promotion of language and traditional integration in educational structures. Both challenges and possibilities are identified in the implementation of bilingual educational programmes in both nations. Ultimately, it underlines the urgent need to establish educational policies and methods that recognise and value the multiplicity of languages and traditions, aiming to foster equity and holistic development of individuals in pluricultural societies.